2021
DOI: 10.3390/ijerph18041637
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Heterogeneity in Positional Errors: A Comparison of Two Residential Geocoding Efforts in the Agricultural Health Study

Abstract: Geocoding is a powerful tool for environmental exposure assessments that rely on spatial databases. Geocoding processes, locators, and reference datasets have improved over time; however, improvements have not been well-characterized. Enrollment addresses for the Agricultural Health Study, a cohort of pesticide applicators and their spouses in Iowa (IA) and North Carolina (NC), were geocoded in 2012–2016 and then again in 2019. We calculated distances between geocodes in the two periods. For a subset, we compu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 34 publications
0
7
0
1
Order By: Relevance
“…The issue of positional error [9] has been explored in medical and spatial geography for data sets most frequently when street addresses were used as the locations of health outcomes [11][12][13]. There are various reasons positional errors arise with these data sources [9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The issue of positional error [9] has been explored in medical and spatial geography for data sets most frequently when street addresses were used as the locations of health outcomes [11][12][13]. There are various reasons positional errors arise with these data sources [9].…”
Section: Discussionmentioning
confidence: 99%
“…Because street segments are often longer in rural areas these errors tend to be larger [9]. Address positional errors have received special attention in exposure studies for rural populations [11][12][13]. In these studies, house addresses had reported positional errors, with 44-72% with errors of at least 100 m and the average positional errors ranged from 200 to >800 meters (with extreme values of 35.6-48.5 km).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, to assess environmental exposures, we collected and geocoded AHS participants’ addresses at each study phase. 18,19 Version 1 geocodes were used for assigning drinking water source and modeling nitrate concentrations in private wells (described below).…”
Section: Methodsmentioning
confidence: 99%
“…These spatial errors are related to the algorithms that convert a place description to geographic coordinates (geocoding) [ 9 , 11 , 12 ] but the consequences for modeling SDMs appeared have been ignored in the applications literature. This issue has been most frequently evaluated when a street address is the key field in geocoding efforts [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%